PERAN EFIKASI DIRI DALAM MEMEDIASI DAMPAK PENGALAMAN DAN GENDER TERHADAP MUTU AUDIT INTERNAL DI INSPEKTORAT PROVINSI BALI - Anak Agung Bagus Amlayasa; Dewa Ayu Kristiantari; I Wayan Kartana; Made Shita Widyantari Kayika Putri (KRISNA: Kumpulan Riset Akuntansi, 2026)
This study aims to analyze the effects of tenure (experience) and auditors’ gender characteristics on audit report quality, with self-efficacy level as a mediating factor. The research was conducted in the working environment of the Regional Inspectorate of Bali Province. Maintaining a standardized audit quality is crucial to ensure the reliability of financial data while preserving the institution’s credibility in the public eye. Although previous studies have examined various determinants of audit quality, the discussion of the cognitive confidence aspect (self-efficacy) in this interaction remains relatively limited. Using a quantitative method with a cross-sectional survey, this study involved the entire population of internal auditors at the institution, totaling 57. Data collection used a structured, reliable questionnaire, which was then processed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis techniques. The modeling results demonstrate the significant positive impact of work experience and gender diversity variables on the quality of released audits. Furthermore, self-efficacy is a valid mediating variable that strengthens the influence of these two individual characteristics on assignment outcomes. These findings indicate that examiners with extensive experience and certain gender characteristics tend to produce more accurate audit recommendations, where strong self-confidence reinforces their professionalism. Practically, this research provides a new direction for public institution management regarding the urgency of investing in employee work mentality strengthening (self-efficacy) programs to optimize public sector oversight functions in Indonesia.